A STUDY ON PREFERENCE OF POLICYHOLDERS ABOUT PUBLIC AND PRIVATE LIFE INSURANCE COMPANIES IN TIRUNELVELI DISTRICT - Meenakshi, I. (International Journal of Research -GRANTHAALAYAH, 2018)
There are currently, a total of 24 life insurance companies in India. Of these, Life Insurance Corporation of India (LIC) is the only public sector insurance company. All others are private insurance companies. The Life Insurance Corporation of India (LIC) is the largest life insurance company in India and also the country’s largest investor. More and more new private insurance companies are coming up year after year. And, these new and private life insurance companies adopt aggressive marketing strategies to introduce their products and to tap the potential policyholders. It is witnessed that new policies like ULIPs are introduced by these new private life insurance companies. It is in this concept this study has been undertaken to assess and analyze the preference of policyholders towards insurance services offered by public and private life insurance companies in Tirunelveli district.